Inversion of Dopamine Responses in Striatal Medium Spiny Neurons and Involuntary Movements - Liang, Li (Society for Neuroscience, 2008)
Dopamine influence in the striatum is essential to motor behavior and may lead to involuntary movements in pathologic conditions. The basic mechanisms lie in differential dopamine responses of medium spiny neurons (MSNs) contributing to striatal output pathways. The relationship between striatal discharge and mobility is thus critical to understanding the actions of dopamine. Using extracellular recordings in severely parkinsonian monkeys, we examined the activity changes of MSNs during different levels of dopamine stimulation. The activity of single MSNs was recorded continuously throughout conditions of parkinsonian disability, its reversal, and the exhibition of involuntary movements after levodopa administration. Parkinsonian disability was associated with robust and widely distributed increases of MSN firing. In the parkinsonian state, dopamine influx produced both increases and decreases in the discharge rate of MSNs. Furthermore, in contrast to the expected net reduction of activity, dopamine-induced recovery of mobility occurred with predominant further increases of neuronal activity. In contrast, involuntary movements were associated with a distinctive inversion of the dopamine responses. The activity increases and decreases associated with the recovery of mobility were subsequently inverted in a number of neurons, and these bidirectional changes created large differences of discharge across MSNs. Thus, a markedly dysregulated state of striatal activity develops after chronic dopamine denervation and, in such a state of MSN activity, dopamine induces altered and disproportionate responses. These findings point to the fundamental role of dopamine-mediated balance of striatal outputs for normal movement.